PENERAPAN PENDEKATAN PEMBELAJARAN OPEN ENDED UNTUK MENINGKATAKAN PEMAHAMAN SISWA KELAS V AL ANKABUT SDIT AL FAHMI PALU PADA MATERI OPERASI HITUNG BILANGAN BULAT - Agung Wicaksono (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2021)
The background of this research is that generally students understand the concept of multiplication and division of integers by memorizing. Basically, the memorization method will be appropriate if you memorize it, you know and understand what you have memorized. So that students do not just memorize alone. However, students really understand what they have memorized, and the teacher in providing material on multiplication and division of integers is only glued to the textbook but does not use other solutions that are easier for students to understand. To improve students' understanding of the operations of multiplication and division of integers, learning uses an Open-Ended approach that designs a solution and answer in the operation of multiplication and division of integers with more than one solution and answer. The main objective of this research is to find out how big the Open-Ended learning approach is in improving the understanding of fifth grade students of Al Ankabut SDIT Al Fahmi on the operations of multiplication and division of integers. In this study, the researcher conducted classroom action research with six students as research subjects who were selected based on their ability level, consisting of six students, namely two students with low abilities, two students with moderate abilities, and two students with high abilities. The process of collecting data was done through tests, observations, interviews and field notes. The action was carried out four times, namely Action (1) was learning about all the elements in multiplication using Open-Ended learning through a structural approach. Action (2) is learning about integer multiplication operations with the application of Open-Ended learning through a structural approach. Action (3) is learning about all the elements in the division using Open-Ended learning through a structural approach. Action (4) is learning about the operation of dividing integers by applying Open-Ended learning through a structural approach. The results show that learning with an Open-Ended approach can improve the understanding of fifth grade students at Al Ankabut SDIT Al Fahmi Palu in the operations of multiplication and division of integers.